Unravelling the genetic architecture of human complex traits through whole genome sequencing - Ozvan Bocher; Cristen J. Willer; Eleftheria Zeggini (Nature Communications, 2023)
Whole genome sequencing has enabled new insights into the genetic architecture of complex traits, especially through access to low-frequency and rare variation. This Comment highlights the key contributions from this technology and discusses considerations for its use and future perspectives.